Legal Views Related to Steal Marriage (Nyolong) Osing Tribe in Subdistrict of Singojuruh, Regency of Banyuwangi, Province of East Java, Indonesia - Guntoro, Heru; Misdi R, Ayip (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine the legal view of nyolong in the Oseng tribe in Banyuwangi. This study was designed using qualitative research with an emancipatory approach, with marriage theory. Data collection is done through observation, in-depth interviews, and documentation studies and literature studies. The analytical method used is descriptive. The results of the research are the factors causing the occurrence ofmarriages nyolong and the settlement process ofmarriages nyolong in the Singojuruh community. is a man who fled a woman who would be made a wife without the knowledge of the female parents without an application or proposal process, while the process of settling amarriage nyolong in the Singojuruh oseng community was after the theft or helping the male send one of his closest relatives to convey the occurrence of female theft to women's parents / families, the families of men and women negotiating to complete the next process, and discuss the implementation of the marriage procession.